Religious studies approaches to the intersection of artificial intelligence and religion: formations analogous to religion - Rähme, Boris; Prohl, Inken (Religion, 2025)
This article investigates the intersections of religion and artificial intelligence (AI), exploring how AI evokes religious narratives, shapes religious practices, and generates formations analogous to religion. The concept of formations analogous to religion is developed as a critical framework for understanding AI’s religious and cultural implications. It is argued that AI’s cultural significance is often mediated through religious language and symbolism. The article provides an overview of current research and outlines working definitions of AI, religion, and formations analogous to religion. The contributions to this thematic issue are introduced by identifying their key points of convergence: the mystification of AI in narratives and discourses, which can obscure ethical issues and reinforce power imbalances; the integration of AI into religious practices, which can lead to novel formations analogous to religion; and the ‘re-enchantment’ of the digitally suffused world via AI’s perceived autonomy and agency, which creates new modes of human heteronomy.
Gesehen am 01.07.2025